Annual Cycles of Sea Ice Motion and Deformation Derived From Buoy Measurements in the Western Arctic Ocean Over Two Ice Seasons. Issue 6 (11th June 2020) - Lei, Ruibo; Gui, Dawei; Hutchings, Jennifer K.; Heil, Petra; Li, Na
Abstract: Data collected by two buoy arrays that operated during the ice seasons of 2014/2015 and 2016/2017 were used to characterize annual cycles of ice motion and deformation in the western Arctic Ocean. An anomalously strong and weak Beaufort Gyre in 2014/2015 and 2016/2017 induced generally anticyclonic and cyclonic sea ice drift during 2014/2015 and 2016/2017, respectively. Cyclonic ice motion resulted in higher contributions of ice divergence to total ice deformation in 2016/2017 than in 2014/2015. In 2014, the autumn ice concentration and multiyear ice coverage were higher than in 2016; consequently, the response of ice motion to wind forcing was weak, and less ice deformation was observed in autumn 2014. During the autumn‐winter transition, the ice‐wind speed ratio, ice deformation rate and its spatial and temporal scaling exponents, and localization of ice deformation decreased markedly in both 2014/2015 and 2016/2017 as a result of freeze‐up and consolidation of ice floes. Such dynamic behavior was maintained through to spring with the further thickening of ice cover. Ice deformation increased due to weakened ice strength as summer approached. The amplitude of the annual cycle of ice deformation rate in the western Arctic Ocean in 2014/2015 and especially in 2016/2017 was larger than that observed during the Surface Heat Budget of the Arctic Ocean (SHEBA) program in 1997/1998. We attribute this phenomenon to ice loss during the recent summers, especially of thick multiyear ice. Plain Language Summary: Loss of multiyear sea ice may give rise to a weaker Arctic ice pack, with increased susceptibility to atmospheric and oceanic forcing. Ice drifters deployed in the summers of 2014 and 2016 were used to characterize the annual cycles of sea ice motion in the western Arctic Ocean. There were large differences in the atmospheric and also the sea ice conditions between 2014/2015 and 2016/2017. Compared to the 2014 summer, the more rapid loss of Arctic sea ice in summer 2016 preconditioned the freezing season to have a stronger response to winds, affecting sea ice dynamics. Nevertheless, the annual amplitude of ice deformation during both 2014/2015 and 2016/2017 exceeded that during SHEBA in 1997/1998, likely due to the higher ice loss in recent summers. Summer Arctic sea ice dynamics are enhanced compared to that in winter, and the seasonal amplitude of ice deformation increases as summer ice reduces. This is mirrored by the increased amplitude in seasonal cycle for ice thickness. We infer that with the lengthening of the ice melt season, ice motion will resemble free drift conditions earlier during late spring and later in autumn. Key Points: Buoy arrays from two ice seasons, 2014/2015 and 2016/2017, with differing Beaufort Gyre patterns were used to characterize ice deformation Extremely low ice concentration during summer 2016 had a long‐lasting effect on ice deformation during the subsequent ice growth season Annual amplitude of ice deformation rate during each ice season exceeded that in 1997/1998 because of higher ice loss in recent summers